2020
DOI: 10.1002/macp.201900516
|View full text |Cite
|
Sign up to set email alerts
|

Supersoft, Stretchable, Tough, and Adhesive Elastomers with Dual Metal‐Ionic Crosslinked Double‐Network Structure

Abstract: Soft, stretchable, tough, and adhesive elastomers are developed based on the metal‐ionic crosslinked double network structure, where the metal ion coordination of sulfonated poly(phenylene oxide) (SPPO) is used for the first network and the soft chemical crosslinked poly(ethyl acrylate) (PEA) is used for the second network. The influence of SPPO content on the tensile, cyclic tensile, adhesive, and rheological behavior of the elastomers is systematically investigated. It is observed that the elastomers are imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…They use Al-COOH ion binding to construct a strong polymer network and EU-iminodiacetate (IDA) coordination to construct another weak yet dynamic network structure, resulting in a strong, self-healing IPN elastomer. Similarly, a tough, flexible, stretchable, and adhesive DN elastomer is developed based on metal-ion cross-linking by Jiang et al [108] The first sacrificial network is a sulfonated poly (phenoxy) (SPPO) metal-ion cross-linked network, while the second is a chemically cross-linked poly(ethyl acrylate) (PEA) network (Figure 9a). The hydration of SPPO and the formation of interchain ionic complexation promote the expansion and shrinkage of the elastomer in water and FeCl 3 solution, respectively (Figure 9b).…”
Section: Coordination Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They use Al-COOH ion binding to construct a strong polymer network and EU-iminodiacetate (IDA) coordination to construct another weak yet dynamic network structure, resulting in a strong, self-healing IPN elastomer. Similarly, a tough, flexible, stretchable, and adhesive DN elastomer is developed based on metal-ion cross-linking by Jiang et al [108] The first sacrificial network is a sulfonated poly (phenoxy) (SPPO) metal-ion cross-linked network, while the second is a chemically cross-linked poly(ethyl acrylate) (PEA) network (Figure 9a). The hydration of SPPO and the formation of interchain ionic complexation promote the expansion and shrinkage of the elastomer in water and FeCl 3 solution, respectively (Figure 9b).…”
Section: Coordination Interactionsmentioning
confidence: 99%
“…e) Adhesive properties of the DN elastomers. Panels (a)-(e) are reproduced with permission [108]. Copyright 2019, Elsevier.…”
mentioning
confidence: 99%
“…In addition to mentioned strategies, the interpenetrating polymer network is also beneficial to improving the mechanical properties. [ 42 ] It has been previously confirmed that the interpenetrating network is superior to the single network when comparing peak stress and fracture toughness. [ 43 ] Moreover, the mechanical strength can be significantly improved by incorporating nano‐particle and nano‐fiber.…”
Section: Supramolecular Adhesives With High Bonding Strengthsmentioning
confidence: 99%
“…( b ) Summary of mechanical properties of the SCDCEs. ( c ) Ashby plot of the mechanical properties of SCDCEs and recently reported acrylate-based elastomers [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Cyclic stress–strain curve of SCDCE-0.3 ( d ), SCDCE-0.5 ( e ) and SCDCE-0.8 ( f ).…”
Section: Figurementioning
confidence: 99%